Physical examination of the spine - Albert, Todd J. (Thieme, 2017)
"From the authors of the bestselling Spine Surgery: Tricks of the Trade, here is the concise "how-to" guide on conducting diagnostic spine exams. The text begins with a thorough review of the fundamentals, including basic anatomy and neurology, and goes on to systematically outline tests for the cervical, thoracic, and lumbar spine. It is an ideal resource for both beginners and practicing physicians."